NILAI-NILAI KERJA DAN KOMITMEN ORGANISASI: SEBUAH STUDI DALAM KONTEKS PEKERJA INDONESIA - Meiyanto, Sito; Santhoso, Fauzan Heru (Faculty of Psychology, Universitas Gadjah Mada, 1999)
This research seeks to investigate the correlation between work values and organizational commitment in the Indonesian context. Two major dimensions of work values, that is intrinsic and extrinsic, were derived from a factor anaysis of Wollack’s scale. Organizational commitment was defined in terms of an individual’s degree of identification and involvement in the work organization. The study is based on 470 samples with correlational data for the relationships between organizational commitment and work values. The total sample was derived from four different companies and type of the production. The findings reveal that the correlational relationship between work values and organizational commitment is significantly positive. In general, the intrinsic work values scale is related more to commitment than the extrinsic work values scale. Thus, it may be fair to say that work values which have been demonstrated to be related to commitment in the Western industrial societies also hold true in the Indonesian context. Besides the intrinsic work values scale, demographic characteristics appeared to have a strong and statistically significant relationship with commitment, except for gender. The implication of the research stems from (1) the finding that work values have a moderately strong correlation with the variable of organizational commitment and (2) that the intrinsic work value scale has a statistically significant and strong relationship than either the extrinsic work value scale or the demographic variables with organizational commitment. As work values is related to commitment, organizations that wish to enhance the commitment of their employees should ensure a congruence between organizational rewards and the work values of employees. Keywords: Commitment, work-value